The Association Between Gestational Hypertension and the Incidence of Neonatal Asphyxia in Kalibaru - ASLINA, WIWIT INDRIYANI; Lestari, Nita Indah; Amalia, Silviatul (JOURNAL EDUCATIONAL OF NURSING(JEN), 2025)
Maternal hypertension, including gestational hypertension, is recognized as a significant risk factor for adverse neonatal outcomes. However, empirical evidence regarding this relationship within the Indonesian healthcare setting remains limited. This study aimed to determine the association between gestational hypertension and the incidence of neonatal asphyxia in Kalibaru. A retrospective cross-sectional study was conducted involving 216 respondents selected through simple random sampling from a population of 469 parturient women. Inclusion criteria encompassed: (1) parturient women with complete medical records at Kalibarukulon Primary Health Center; (2) parturient women with gestational hypertension; and (3) gestational age ≤38 weeks. Data analysis was performed using Chi-Square test with SPSS version 25. The study demonstrated a highly significant association between gestational hypertension and neonatal asphyxia (p-value = 0.000; χ² = 210.699). All respondents with gestational hypertension (100%; n=53) delivered infants with neonatal asphyxia, whereas only 0.6% (n=1) of mothers without gestational hypertension delivered asphyxiated infants. The prevalence of gestational hypertension was 24.5% (n=53) among the study population. Gestational hypertension constitutes a major risk factor significantly associated with neonatal asphyxia. These findings underscore the critical importance of intensive antenatal monitoring, early detection, and optimal management of gestational hypertension to prevent neonatal asphyxia and reduce neonatal morbidity and mortality.